Redo surgery for extensive chronic type A dissecting aneurysm following a Bentall operation. (2018) - Miyake, Keisuke; Funatsu, Toshihiro; Kondoh, Haruhiko; Taniguchi, Kazuhiro
Highlights: The results of redo surgery on aortic arch are still not satisfactory. Type A aortic dissection after Bentall operation was experienced in this case. Visceral perfusion was maintained only from false lumen without reentry. Modified total arch replacement with long elephant trunk was utilized. Aortic fenestration was done for visceral perfusion after closing primary entry. Abstract: Introduction: Despite the technical improvements, redo surgery on the aortic root and arch is still associated with high morbidity and mortality due to the trauma of repeat open-heart surgery and technical complexity. We present the case of extended chronic type A dissecting aneurysm that developed after a Bentall operation, which was successfully treated by applying a modified long elephant trunk technique and surgical aortic fenestration. Case presentation: A 77-year-old man, who had previously undergone a Bentall procedure and an abdominal surgery, developed a type A aortic dissection. At presentation, the aortic dissection extended from the proximal arch to the terminal aorta, which were treated with an axillobifemoral bypass. After 8 months follow-up, the dissecting aneurysm had extended and the visceral arteries were perfused from the false lumen, without re-entry. We successfully repaired a complicated and extended chronic type A dissecting aneurysm by applying a modified long elephant trunk technique and surgical aortic fenestration. Postoperatively, the thoracic aorta false lumen was thromboexcluded, and the visceral perfusion was preserved through the fenestration. Conclusion: In the treatment of complicated aortic arch diseases especially in redo cases, appropriate strategies are mandatory to achieve optimal outcomes. In the extended aortic dissection without the reentry for visceral perfusion, a primary entry closure may lead to visceral ischemia. Modified long elephant trunk technique combined with fenestration technique may be one of the useful techniques to treat the complicated aortic dissection extending to the terminal aorta.